The influence of brace to chord rotational connection stiffness on stability of the truss - Krajewski, Marcin (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The paper is devoted to numerical analysis of the roof truss subjected to upward wind loading and braced at the tensioned top chord. Linear buckling analysis was performed for the beam and shell model of the structure. As a result, the influence of rotational connection stiffness between the brace and the top chord on truss stability was noted. A bi-axial strength testing machine was used to conduct the experimental tests of the rotational connection stiffness between selected steel profiles. The results in the form of measured structural displacements and rotations were presented. The static nonlinear analysis results obtained for the shell model of the structural connection were compared to the results obtained on the experimental set-up.